Oral alterations in patients submitted to antineoplastic therapy for malignant head and neck neoplasms - Edla Layanne Florêncio de Carvalho; Érika Calixto de Souza; Cláudia Cristina Brainer de Oliveira; Danielle Lago Bruno de Faria (Associação Brasileira de Odontologia, 2018)
Objective: To identify the main oral manifestations in patients submitted to treatment for malignant neoplasms in the head and neck region at a center of oncology in Pernambuco. Materials and Methods: This is an observational, cross-sectional, retrospective study carried out at the Caruaru Oncology Center, through the analysis of 50 charts of patients seen in the Dentistry sector in the treatment of cancer in the head and neck region. There was no exclusion according to the sex of the patients, and the sample number was determined for convenience. The medical records that lacked information about the treatment, as well as the medical records of those patients who abandoned treatment with the dental team were excluded. Results: Of the patients, 74% were male, 80% were smokers and 72% were alcoholics. All patients received guidance on oral care, however, 50% of them received these guidelines only during anti-neoplastic treatment. The main oral alteration was mucositis (70%), followed by xerostomia (54%), dysgeusia (50%) and dysphagia (48%). Radiation cavities and osteoradionecrosis occurred in only 2% of patients. Conclusion: All patients received guidance on oral care by a dentist, but most received this information during anti-neoplastic treatment. Several oral alterations associated with antineoplastic treatment were observed, with oral mucositis being the most frequent manifestation.